Performance Evaluation of Industrial Internet of Things Services in Devices of Cloud-Fog-Dew-Things Computing] - Garrocho, Charles; Cavalcanti, Carlos Frederico; Oliveira, Ricardo Augusto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2020)
A large amount of data, called the big data, generated by the devices that are part of the Industrial Internet of Things (IIoT), is expected for years to come. This scenario creates challenges for sending, processing, and storing all data centrally in the cloud. Recent work proposes to decentralize the processing and storage of data to nearby devices to solve these challenges. This paradigm, called dew computing, gained attention in the academy, being developed and evaluated in several areas of application. However, no study has evaluated dew computing in the IIoT environment in practice. To fill this gap, we developed a proof of concept for IIoT to assess aspects of processing and communication between cloud, fog, dew, and IIoT devices. The results of this evaluation showed that dew and IIoT devices could cooperate in the decentralization of cloud computing and help reduce the negatives impact of big data.